HOW BRITISH AND AMERICAN ENGLISH SHAPE THE LEARNER’S THINKING, CONFIDENCE, AND SOCIAL BEHAVIOR - Toshtemirov Akbarjon Ravshan oʻgʻli (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: The distinction between British and American English extends far beyond mere vocabulary and pronunciation differences, profoundly influencing how language learners develop cognitive patterns, self-assurance, and interpersonal behaviors. This study examines the multifaceted impact of choosing between these two major English variants on learners’ psychological and social development. Through analysis of pedagogical research, sociolinguistic studies, and educational statistics, this paper demonstrates that the selection of either British or American English as a learning model significantly affects learners’ thought processes, communication confidence, and cultural identity formation. Research indicates that approximately 1.5 billion people worldwide are learning English, with the majority gravitating toward American English due to media exposure and globalization trends. However, learners who study British English often demonstrate different linguistic attitudes and social perceptions. This investigation explores how phonological variations, lexical choices, grammatical structures, and cultural contexts embedded within each variant shape learners’ cognitive frameworks, influence their self-perception in cross-cultural communication, and determine their social integration patterns. The findings reveal that language variant selection creates distinct psychological imprints on learners, affecting their international mobility, professional opportunities, and intercultural competence.